Review on Abutilon Indicum (Linn.) Sweet (Atibala) - An Important Herb in Ayurveda - ram, Sukha; Kotecha, Mita; Chaudhary, Krutika (International Research Journal of Ayurveda & Yoga, 2021)
Background: Abutilon indicum (Linn.) Sweet commonly known as Kanghi and Atibala, belonging to family malvaceae, is very important plant since long in traditional medicine of India and grows in hot and waste places. Ayurveda herb Atibala review is very helpful to achieve Ayurveda literature. Data Source: The material has been collected from various research articles, Vedas, Samhitas and Nighanus and internet sources etc. to the thought of medicinal uses of Atibala. Conclusion: The drug is attributed with Balya, Kantivardhaka, Ojovardhaka, Brinhana, Krimighna, Dahahara, Rasayana, Mridurechana, Vajikara, Kasahara and Vedanahara properties and The review shows that Atibala is used in many complaints like Vatarakta, Vyanga, Vata-Vyadhi and Nilika etc. in Samhitas it is used in different form of drug i.e. Kalka, Kwath, Churna, Taila and Ghrita etc. in different Ayurveda Samhitas and Nighantus. It is used in Ayurveda medicines from a very long time. The study review highlights its description in Vedas, Samhitas and Nighantus.